2022
DOI: 10.1021/acssensors.2c01100
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Selectivity in Detection of Ionized Perfluoroalkyl Substances at Micro-Interfaces between Immiscible Electrolyte Solutions

Abstract: Widespread contamination by per-and polyfluoroalkyl substances (PFAS) and concern about their health impacts require the availability of rapid sensing approaches. In this research, four PFAS, perfluorooctanoic acid (PFOA), perfluorobutanesulfonic acid (PFBS), perfluorohexanesulfonic acid (PFHxS), and perfluorooctanesulfonic acid (PFOS), were studied at micropipette-based interfaces between two immiscible electrolyte solutions (μITIES) to assess the potentiality for their detection by ion transfer voltammetry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Asymmetric CVs were obtained in all cases, with steady-state voltammograms on the forward sweep (due to radial diffusion to the pores holding the μITIES), scanning from positive towards negative potentials, while the reverse-direction scans are peak shaped (due to linear diffusion within the pores), in agreement with previous studies. 67,68 CV also indicated no adsorption, emulsification, or instability of the interface. 67 In all cases, the reverse peak currents increased linearly with the PFOA concentration in the studied ranges (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Asymmetric CVs were obtained in all cases, with steady-state voltammograms on the forward sweep (due to radial diffusion to the pores holding the μITIES), scanning from positive towards negative potentials, while the reverse-direction scans are peak shaped (due to linear diffusion within the pores), in agreement with previous studies. 67,68 CV also indicated no adsorption, emulsification, or instability of the interface. 67 In all cases, the reverse peak currents increased linearly with the PFOA concentration in the studied ranges (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…67 A recent study assessed the prospects for selectivity in the detection of PFAS mixtures by ion transfer electrochemistry at a micropipette-based μITIES. 68 Whilst PFOS can be detected sensitively at a μITIES array, 67 no studies were reported on PFOA detection at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Surface imprinting of low-molecular-weight compounds can be achieved by depositing and imprinting a polymer layer directly on an electrode surface via electropolymerization, which is a particularly useful method in combination with electrochemical transducers [ 113 , 114 ]. By cycling the potential in a predetermined range with a given sweep rate, the electroactive monomer (such as aniline, o-phenylenediamine, and pyrrole) will be electropolymerized and the substrates will be coated by a very thin layer of polymer [ 81 , 92 , 115 ].…”
Section: Pfas Sensing With Receptors Made Via Imprinting Technologymentioning
confidence: 99%
“…47 Despite some disadvantages of the ITIES, such as instability and high capacitance, improvements have progressed by miniaturisation 48,49 to microscale and by mechanical support with porous membranes or gelled organic phases. [50][51][52][53][54] As a result, PFAS electrochemical detection and sensing has been investigated at the ITIES [55][56][57][58] including the microITIES (µITIES). 55,59 We have previously reported the sensitive detection of PFOA with this approach and identified the impact of matrix components on the electrochemical detection of PFOA.…”
Section: Introductionmentioning
confidence: 99%